PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN KARAKTERISTIK PERUSAHAAN TERHADAP MANAJEMEN LABA - Ita Trisnawati; Valensia (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study was to obtain empirical evidence about the effect of the independent variables namely managerial ownership, institutional ownership, firm size, leverage, profitability, sales growth, and free cash flow on earnings management as the dependent variable. The population of this research are non-financial firms that listed in Indonesia Stock Exchange (IDX) during the period of 2019 until 2021. This study uses a total sample of 116 companies or 348 data for 3 periods. The sample selection in this study used purposive sampling and the analysis of this research test used multiple regression methods. The results of this study indicate that profitability and free cash flow have an effect on earnings management, meanwhile managerial ownership, institutional ownership, firm size, leverage, sales growth have no effect on earnings management.